THE ROLE OF GENETIC VARIATION SINGLE NUCLEOTIDE POLYMORPHISM T45G AND SINGLE NUCLEOTIDE POLYMORPHISM G276T OF THE ADIPONECTIN GENE IN FATTY LIVER PATHOMECHANISM ON OBESE MALE SUBJECT - A, Sulaeman; S, Wahid; A, Sulaiman; Sg, Lawrence (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: The aim of this study was to observe the role of genetic variation T45G and G276T of adiponectin gene in pathomechanism of fatty liver on obese subjects. Methods: An observational study with caseâ€“control design was conducted on 94 obese male subjects (50 subjects are obese male with fatty liver and 44 subjects are obese male without fatty liver). The research is taken place in Prodia Clinical Laboratory Makassar to determine genetic variation single nucleotide polymorphism (SNP) T45G (Genotype TT, thyroglobulin [TG], and GG) and SNP G276T (Genotype GG, GT, and TT) of adiponectin gene, technique of polymerase chain reaction-restriction fragment length polymorphism was used. The level of adiponectin, soluble tumor necrosis factor-Î± receptor 2 (sTNF-Î±R2), and insulin serum were measured by enzyme-linked immunosorbent assay method, meanwhile, fatty liver was detected by ultrasonography. Results: The result of the study showed genetic variation, T45G of adiponectin gene was genotype TT 62.8 %, genotype TG 30.9%, and genotype GG 6.3%; meanwhile, genetic variation G276T of adiponectin gene was genotype GG 43.6%, genotype GT 38.3 %, and genotype TT 18.1 %. There was no significant correlation of genetic variation T45G as well as G276T of adiponectin gene, to the level of adiponectin serum (>0.05). Insulin resistance was more frequent on genotype TT genetic variation T45G of adiponectin gene as compare to that on TG+GG (p=0.069). Genotype TT on genetic variation T45G of adiponectin gene was significant correlated with fatty liver (p=0.010). Genotype TG+TT on genetic variation G276T of adiponectin gene was more likely to have insulin resistance and fatty liver than that of genotype GG. Allele T carrier on genetic variation T45G and G276T of adiponectin gene had a higher chance to have insulin resistance and fatty liver as compare to that of allele G carrier. The odds ratio of having fatty liver insulin resistance is 5.3, genotype TT on genetic variation T45G of adiponectin gene is 3.8, low level of adiponectin is 3.4, and high level of sTNF-Î±R2 is 3.3. Conclusion: Genotype TT on genetic variation T45G of adiponectin gene has a role in fatty liver on obese subjects. Genotype TG+TT on genetic variation G276T of adiponectin gene was more high frequent to have fatty liver compare to that on genotype GG. Allele T carrier on genetic variation T45G of adiponectin gene had higher frequency on the occurrence of insulin resistance than that on allele G carrier. Insulin resistance has the highest influence as compare to genotype TT on genetic variation T45G of adiponectin gene, low level of adiponectin serum, high level of sTNF-Î±R2 serum in the pathomechanism of fatty liver in obese subjects.